Drug:Depth Classification - Ranganathan, S. R.; Neelameghan, A. (Journal of Information and Knowledge, 1964)
Works out a scheme for the classification of the subjects going with the (BC) "F56 Technology of Drug" and the (BC) "LX3 Pharmacology", based on the design principles outlined in Paper A of this volume. The schedules given are confined to the first characteristics for [IP] only. A single set of (Q1) is given for the subjects going with either of the (BC) Technology of Drug or the (BC) Pharmacology. Gives an alphabetical index to the schedule. Gives a classified list of 39 examples classified according to the above scheme.